2016
DOI: 10.1099/jgv.0.000558
|View full text |Cite
|
Sign up to set email alerts
|

Identification of human cytomegalovirus in tumour tissues of colorectal cancer and its association with the outcome of non-elderly patients

Abstract: Increasing evidence suggests that human cytomegalovirus (HCMV) plays an oncomodulatory role in human cancers. In colorectal cancer (CRC), presence of HCMV in tumours has been associated with a poor outcome in elderly patients. This study aimed to investigate the association between HCMV and the outcome of non-elderly patients with CRC. In tumour samples, HCMV DNA was detected by PCR. Viral transcript and protein were detected by in situ hybridization (ISH) and immunohistochemical staining (IHC), respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Additionally, higher transcription of IL‐17 was found in CMV‐positive tumours, which correlates with a poor outcome of CRC . On the contrary, presence of CMV in CRC tumours among patients < 65 years of age independently predicted a higher disease‐free survival rate based on multivariate Cox proportional hazards analysis . In this study, significant intra‐tumoral inflammatory responses were more frequently observed in CMV‐positive tumours with lower levels of IL‐1, a pleiotropic cytokine implicated in promoting tumour growth, angiogenesis and potentially metastasis .…”
Section: Cmv‐specific Memory Inflation Shapes Global and Anti‐tumour mentioning
confidence: 53%
See 1 more Smart Citation
“…Additionally, higher transcription of IL‐17 was found in CMV‐positive tumours, which correlates with a poor outcome of CRC . On the contrary, presence of CMV in CRC tumours among patients < 65 years of age independently predicted a higher disease‐free survival rate based on multivariate Cox proportional hazards analysis . In this study, significant intra‐tumoral inflammatory responses were more frequently observed in CMV‐positive tumours with lower levels of IL‐1, a pleiotropic cytokine implicated in promoting tumour growth, angiogenesis and potentially metastasis .…”
Section: Cmv‐specific Memory Inflation Shapes Global and Anti‐tumour mentioning
confidence: 53%
“…136,137 On the contrary, presence of CMV in CRC tumours among patients < 65 years of age independently predicted a higher disease-free survival rate based on multivariate Cox proportional hazards analysis. 138 In this study, significant intra-tumoral inflammatory responses were more frequently observed in CMV-positive tumours with lower levels of IL-1, a pleiotropic cytokine implicated in promoting tumour growth, angiogenesis and potentially metastasis. 139,140 Taken together, CMV may enhance immunity to cancer in younger patients whereas longterm CMV infection may be detrimental to clinically relevant anti-tumour immune responses in older individuals ( Fig.…”
Section: Colorectal Cancermentioning
confidence: 56%
“…In human malignant glioma, which is the most studied HCMV-associated tumor, HCMV infection is mainly regarded as a tumor promoter (42,43). However, previous studies have revealed that HCMV may be a protective factor in the outcome of gastrointestinal tumors, breast cancer and hepatocellular carcinoma (44)(45)(46)(47). Furthermore, the HCMV genes US28 (48) and UL123 (49) can accelerate tumor growth and enhance cancer cell stemless, while UL138 can promote the apoptosis of cancer cells (17).…”
Section: H Pylori --------------------------------------------------mentioning
confidence: 99%
“…The detailed evaluation of the 67 remaining studies resulted in the further exclusion of 57 due to duplicated publications, lack of adequate data, or no original date for the meta-analysis. Finally, 10 publications were included in our meta-analysis [11,[16][17][18][19][20][21][22][23][24]. The study selection process has been depicted as a flow chart in online supplementary Figure 1 (for all online suppl.…”
Section: Meta-analysis Of Hcmv Prevalencementioning
confidence: 99%